Foodborne diseases : a study before and during the COVID-19 pandemic in Brazil - Nepomuceno, Fernanda Vinhal (2023)
Foodborne Diseases (FBDs) are a worldwide problem and occur after contaminated food has been ingested, signaling a lack of food quality. Even though the SARS-CoV-2 virus is not transmitted through food, the COVID-19 pandemic has caused several challenges worldwide that have had direct implications on food production and handling, stimulating and reinforcing the adoption of good manufacturing and food handling practices. The aim of this study was to analyze data on notifications of FBD in Brazil in the years before (2018 and 2019) and during (2020 and 2021) the COVID-19 pandemic. Secondary data from the National System of Notifiable Diseases was analyzed, evaluating: overall incidence rate, lethality and mortality, contamination sites, and criteria for confirming the etiological agent. There were 2206 records of FBDs, and the mortality rate was 0.5% in both periods. The incidence rate before the pandemic was 6.48 and during the pandemic was 3.92, while the mortality coefficient was 0.033 before and 0.019 during the pandemic, both per 100,000 inhabitants. There was no significant difference in the number of FBD notifications in the evaluated periods. There was a migration of the location of FBD, with a significant increase in FBD notifications in hospitals and health units and a reduction in notifications from social events. There was a significant increase in the type of criteria used to confirm outbreaks, with an increase in clinical laboratory tests and clinical reports for bromatology. The increase in notifications in hospitals and health units demonstrates the necessity of improving food safety knowledge and the attitudes and practices of food handlers and healthcare professionals.